Africa's Data Privacy Puzzle: Data Privacy Laws and Compliance in Selected African Countries - Kaddu, Sarah; Ssekitto, Francis (University of Dar es Salaam Library Journal, 2024)
This study sought to give a thorough analysis of data privacy legislation, compliance rates, enforcement strategies, and related issues in seventeen (17) African countries that were chosen for the study. The study's objectives were to assess the state of data privacy laws in selected African countries, analyse levels of compliance among entities operating within these countries, assess the effectiveness of enforcement mechanisms, and identify and analyse the common challenges African countries face in complying with and enforcing data privacy laws. Researchers conducted a systematic review of 48 data privacy publications to gain a deep understanding of the complex data privacy landscape. This involved rigorous criteria for inclusion/exclusion, comprehensive search strategies, quality assessment, and data extraction/synthesis. While 15 African countries have implemented comprehensive data privacy legislation, two (Ethiopia and Burundi) rely on general regulations. The analysis found that regulatory bodies significantly enhance compliance, and highlighted recurring challenges such as insufficient public awareness, resource limitations, and complex governance structures. The research underscores the crucial role of dedicated legislation, public education, empowered regulatory authorities, and regional collaboration in guaranteeing data privacy rights in the digital age across Africa.